Three Iranian Loanwords in Late Babylonian Texts - Stolper, Matthew W.
ḫanbara ‘storehouse’; upiātu, uppaiāta, probably a royal impost on commodities and/or the store of such commodities for crown’s use; kalammaru, karammaru, karri ammaru ‘registry’.